Strategi Manajemen Kepala Sekolah dalam Mengatasi Kurangnya Tenaga Pendidik - Riani N. Ninef; Jumiati Sakan; Candra Biar; Ledi Rido; Fanto Tanaem; Yanti Y.E Sole (Indo Publishing, 2026)
This study examines the management solutions used by school administrators to solve the instructor shortage in educational institutions. The problem of teacher shortages has emerged as a significant barrier that impedes the learning process, diminishes the quality of education, and obstructs the attainment of institutional objectives. This study employs a qualitative methodology using a literature review, analysing scientific publications from 2012 to 2016, including books, journals, research papers, and pertinent articles. The study findings indicate that the educator shortage is attributed to the unequal distribution of instructors, constrained financial resources, diminished job motivation, elevated teacher turnover rates, and inequities in welfare. To resolve this problem, the school principal instituted many strategic measures: optimising current human resources, using a flexible staffing structure, enhancing welfare and motivation, forging collaborations, and advancing professional abilities. This study suggests that efficient management requires thorough planning, robust leadership, and collaboration among stakeholders. This technique guarantees the sustainability and quality of education despite constrained human resources.